Security informed safety assessment of industrial FPGA-based systems - Kharchenko, V.; Illiashenko, O.; Brezhnev, E.; Boyarchuk, A.; Golovanevskiy, Vladimir (Techno-Info Comprehensive Solutions (TICS), 2014)
The strong interconnection and interrelation of safety and security properties of industrial system which are based on programmable logic (field programmable gate arrays, FPGA) is reviewed. Information security, i.e. system's ability to protect the information and data from unauthorized access and modification, is a subordinate property with respect to safety of many instrumentation and control systems (I&Cs), primarily to the NPP reactor trip systems. Such subordination may be taken into account by implementation of security informed safety (SIS) approach. The methodology for safety assessment of FPGA-based systems which are widely used in industrial critical systems is described. It is based on joint using of security analysis techniques (GAP-analysis and intrusion modes, effects and criticality IMECA analysis) and also their reflection on the final safety assessment picture of the system with two channels. This methodology forms so called security informed safety approach. Additional aspects of safety assessment of diverse instrumentation and control FPGA-based systems for safety-critical application are described.